Design and developement of aquatic locomotion on robotic fish - HUANG, ZHIXIN (2014)
Various research projects have been conducted to create efficient, maneuverable, and environmentally friendly underwater propulsion systems. Adapting designs from the nature, this bio-mimetic mechatronics project aimed to develop a robotic shark with pectoral, caudal and dorsal fins which are most essential in the propulsion of a real shark. This project emphasized greatly on the design and development of the robotic shark.